Quantitative influence of solidification path on solute micro-segregation and inclusion precipitation in the solidification process of rail steel - Xinliang Gao; Wenyue Ba; Chenyang Wang; Zhuangzhuang Zhang; Yinlong Wang; Tengfei Li; Zhinan Yang; Fucheng Zhang (Journal of Materials Research and Technology)
A solute redistribution model, which takes the phase transformation and MnS precipitation during the solidification of rail steel into consideration, was established. The influence of solidification path on solute micro-segregation and inclusion precipitation was quantitatively analyzed. Furthermore, the effects of MnS inclusion precipitation, equilibrium distribution coefficient (ki), and back-diffusion coefficient (βi) on solute micro-segregation were investigated. The results indicate that the solidification path significantly influences solute micro-segregation and MnS precipitation in the solidification process. When the carbon content ranges from 0.018% to 0.054%, the peritectic transformation occurs at the end of solidification, and the carbon content significantly affects MnS inclusion precipitation and solute micro-segregation. The carbon content influences solute redistribution through the changes in solidification temperature and phase composition, resulting in the variations in ki and βi, which in turn affects solute micro-segregation. The impact of ki on solute micro-segregation is significantly influenced by phase composition, while βi is affected by both temperature and phase composition. There is a competitive relationship between ki and βi concerning solute micro-segregation. The research findings provide a foundation for further elucidating the laws of solute redistribution during the solidification of molten steel, thereby effectively improving the quality of rail steel casting bloom.